Statistical Analysis Of Pharmaceutical Industry Energy Saving Potential By Benchmarking - Sukono Sungkono; Burhan Bungin; Damelina Basauli Tambunan (Politeknik APP Jakarta, 2025)
This study focuses on identifying and quantifying the potential for energy savings in the pharmaceutical industry through a comprehensive energy audit approach. This analysis enabled the identification of electricity usage patterns, assessment of operational efficiency, and evaluation of overall energy performance indicators. The results reveal a consistent year-over-year increase in energy demand, exceeding the projected electricity supply from the grid. These findings highlight the urgent need for energy optimization strategies, such as the adoption of advanced energy management systems, process optimization, and investment in renewable energy integration, to ensure sustainable operations and mitigate the risks of future energy shortages. By providing actionable insights and quantifiable metrics, this research contributes to supporting decision-makers in the pharmaceutical sector in planning energy-efficient operations and aligning with sustainability goals.